Phenolics and Carotenoid Contents in the Leaves of Different Organic and Conventional Raspberry (Rubus idaeus L.) Cultivars and Their In Vitro Activity - Alicja Ponder; Ewelina Hallmann (MDPI AG, 2019)
Raspberry leaves are a source of carotenoids and polyphenols, including ellagic acid and salicylic acid. The results of scientific research suggest that they have potential pro-health properties that contribute to human health. The aim of this study was to determine the polyphenolic and carotenoid profiles in the leaves of selected raspberry cultivars and their in vitro activity. The second aim was to determine the impact of organic and conventional farm management on the polyphenol, carotenoid, and chlorophyll contents in different raspberry cultivars: ‘Polana’, ‘Polka’, ‘Tulameen’, ‘Laszka’ and ‘Glen Ample’. Compared with conventional raspberry leaves, organic raspberry leaves were characterized by a significantly higher content of dry matter, total polyphenols, total phenolic acids, chlorogenic acid, caffeic acid, salicylic acid and quercetin-3-O-rutinoside; moreover, the organic leaves were characterized by higher antioxidant activity. Among examined cultivars, ‘Polka’ c. was characterized by the highest antioxidant status. However, raspberry leaves from conventional farms contained more total carotenoids, violaxanthin, alpha-carotene, beta-carotene, total chlorophyll and individual forms of chlorophylls: a and b.